Phyto-Tolerance Degradation of Hydrocarbons and Accumulation of Heavy Metals by of Cajanus cajan (Pigeon Pea) in Petroleum-Oily-Sludge-Contaminated Soil - Ibrahim Alkali Allamin; Nur Adeela Yasid; Siti Rozaimah Sheikh Abdullah; Mohd Izuan Effendi Halmi; Mohd Yunus Shukor (Agronomy, 2021)
A pot experiment was conducted to measure the phyto-tolerance and accumulation of heavy metals in petroleum oily sludge POS by Cajanus cajan (pigeon pea) on soils treated with five different concentrations (1%, 2%, 3%, 4%, and 5% w/w) of the POS. The response of the plant to oily sludge varied significantly from the untreated control and among the various treatments. The growth of C. cajan was slightly (but not significantly) influenced by the oily sludge in soil; growth of C. cajan at relatively lower concentrations of POS (1 to 3%) was greater than in the treatments with relatively higher concentrations POS (4 to 5%). A significant interaction was observed in the relative growth rates (RGRs) of C. cajan, which significantly increased in the treatments with relatively low POS (1 to 3%) and decrease significantly at higher POS concentrations. The heavy metal content of the plant roots as the POS concentrations were increase show that the concentration of all heavy metals in the roots increased accordingly. Cu showed the highest accumulation with an increase from 1.9 to 6.8 mg/kg followed by Pb, Zn, Ni, Mn, and Cr, which was the least-accumulated. Heavy metal analysis in C. cajan tissues indicated a considerable accumulation of the metals Pb, Zn, Ni, Mn, Cu, and Cr in the root and stem of the plant, with negligible metal concentrations detected in the plant leaves, suggesting a low translocation factor but indicating that C. cajan is resistant to heavy metals. As the search for more eco-friendly and sustainable remediating green plant continues, C. cajan shows great potential for reclaiming POS-contaminated soil due to the above properties including resistance to toxic heavy metals from oily sludge. These findings will provide solutions to polluted soils and their subsequent re-vegetation.